Transient aspects of the Hadley circulation forced by an idealized off-equatorial ITCZ - González, Alex O. (2017)
This paper presents analytical solutions of large‐scale, zonally symmetric overturning circulations in the tropical free troposphere forced by transient diabatic heating in the off‐equatorial intertropical convergence zone (ITCZ). The dynamics are discussed in the context of the time‐dependent meridional circulation equation arising in an equatorial β‐plane model. The solutions of these differential equations contain terms for the slow, quasi‐balanced part of the response and terms for the transient, zonally symmetric, inertia‐gravity wave part of the response. When the off‐equatorial (north of the equator) ITCZ diabatic heating is switched on at various rates, both parts of the response reveal a basic asymmetry between the southern and northern hemispheres, with the southern hemisphere side containing most of the quasi‐balanced compensating subsidence and transient inertia‐gravity wave activity. The inertia‐gravity waves travel in wave packets that bounce off a spectrum of turning latitudes and are analyzed in the context of an average conservation law approach. These traveling wave packets cause the mass flux in the southern and northern Hadley cells to pulsate on timescales of about 1, 2, and 3 days for diabatic heating of the external, first internal, and second internal vertical modes, respectively. The spectral characteristics of the vertical motion in the ITCZ and subsidence regions are slightly more complicated and depend on ITCZ location.